SAT0501 Influence of MEFV Gene Mutations and R202Q Polymorphism on Inflammatory Clinical Manifestations and Oxidative Stress. (9th June 2015) - Lazarevic, D.S.; Radovic, J.; Debeljak, M.; Toplak, N.; Avcin, T.; Vojinovic, J.
Abstract : Background: Mutations of MEFV gene are considered as the primary cause of Familial Mediterranean Fever but are also found in other multifactorial autoinflammatory and/or autoimmune diseases. Objectives: The aim of our study was to determine the incidence of recurrent fevers and other clinical signs of inflammation in healthy subjects with present mutations and/or R202Q polymorphism of MEFV gene and to compare incidence of this events and oxidative stress parameters with subjects without MEFV changes. Methods: Study was performed as addition to recently published study by Debeljak M et al (Clin Exp Rheum 2015) intended to evaluate distribution of MEFV gene mutations in healthy population of South East Europe. 100 healthy subjects donated blood samples for genetics and oxidative stress parameters analysis. Data about inflammatory clinical manifestations were obtained retrospectively using Eurofever project questionnaire. DNA was extracted from peripheral blood and sequencing was performed using automated sequencer. Oxidative stress was determined by measuring thiobarbituratic acid reactive substances (TBARS) and advanced oxidation protein products spectrophotometrically. Superoxide dismutase (SOD) activity was determined by McCord and Fridovich method and catalase activity using ELISA kit. According the genetic findings patients were stratified into 3 groups:A-with MEFV gene mutations associated with R202Q homozygotes; B-only with MEFV gene mutations and C-only R202Q homozygotes. Results: Out of 100 examined subjects 11% had MEFV gene mutation:6% heterozygous E148Q/N and 5% K695R/N; 10% homozygotes and 45% heterozygotes of R202Q polymorphism.The established carrier frequency of mutations and R202Q polymorphism was unexpectedly high for a healthy population. Group A and B reported more frequently febrile episodes of unknown cause (pA=0.027, pB=0.048), diffuse abdominal pain (pA=0.015, pB=0.017), peritonitis (pA=0.019, pB=0.008) and fatigue (pA=0.012, pB=0.032) in comparison with subjects without these gene changes. Group C had significantly more often repeated episodes of fever (p=0.022), diffuse abdominal pain (p=0.009) and lymphadenopathy (p=0.035). Group A had significantly higher concentration of TBARS compared with persons without gene changes (p=0.03) suggesting the existence of increased oxidative damage. SOD activity was significantly higher in A (p=0.049) and C group (p=0.001), probably due to increased induction of extracellular SOD. Changes in oxidative stress parameters in the MEFV carriers significantly were associated with inflammation parameters: leukocytes count with TBARS (p=0.009) and ESR and SOD levels (p=0.031). Conclusions: Healthy individuals may bear E148Q and K695R MEFV gene mutations and R202Q polymorphism in homozygous state. These gene alterations contribute to a subtile oxidative stress and may be associated with more frequent episodes of fever and unspecific inflammatory manifestations, as a predisposing factor for inflammation. Disclosure of Interest: None declared